Use of Methylphenidate in Excessive Daytime Sleepiness in Alzheimer’s Patients Treated with Donepezil: Case Series - Bidzan, Leszek (Neuropsychiatr Dis Treat, 2020)
Sleep disorders, inversion of sleep rhythm, excessive daytime sleepiness, and sleeplessness at night are common in Alzheimer’s disease (AD). Sleep disorders in AD have a diverse pathogenesis and their incidence increases as the disease progresses. Some publications indicate possible beneficial effects of methylphenidate on sleep. We presented two cases of patients with diagnosed AD accompanied by sleep disorders which had a significant impact on their functioning. The pathogenesis of sleep disorders was different in those two cases. In both case studies, the use of methylphenidate brought an immediate clinical effect, improving sleep at night and functioning during the day.